A POTENTIOMETRIC STUDY OF EU3+ COMPLEXATION WITH ACETATE LIGAND FROM 25 TO 170°C AT P SAT - Zotov A.V.; Tagirov B.R.; Diakonov I.I.; Ragnarsdottir K.V. (My University, 2002)
Thermodynamic properties for europium acetate (EuCH3COO2+ and Eu(CH3COO)2+) complexes were studied by potentiometry at temperatures from 25 to 170°C at the saturation pressure of water. The thermodynamic association constants (K1 and K2) for the reaction Eu3+ + n Acite− = EuAcn3−n. were determined by two different experimental approaches at 25 to 75°C and 75 to 170°C. Logarithms of measured association constants increase with increasing temperature, showing that Eu-Ac complexing increases as temperature rises. Log K1 for EuCH3COO2+ increases from 2.91 at 25°C to 4.25 at 170°C, whereas log K2 for Eu(CH3COO)2+ increases from 4.83 at 25°C to 7.39 at 170°C. Species distribution calculated in this study using the experimentally determined association constants suggests that in acetate-bearing solutions (≥0.05 m) Eu-acetate complexes dominate over the free ion above pH of 4 to temperatures of at least 200°C. At equal total acetate and carbonate concentrations and at 25°C, the relative stability of carbonate and acetate complexes is close. However, as the temperature rises the relative stability of carbonate versus acetate complexes is model dependent.